Advantage or Paradox? The Challenge for Children and Young People of Growing Up Urban - United Nations Children's Fund (United Nations, 2019)
This report by UNICEF reveals that not all children in cities benefit from the so-called ‘urban advantage’—the notion that higher incomes, better infrastructure, and proximity to services grant urban children advantages over rural children. In fact, urban inequality and exclusion among children in cities can make many of the most disadvantaged children in urban areas worse off than children in rural areas. Hence, the ‘urban paradox.’